2008
DOI: 10.1302/0301-620x.90b7.20213
|View full text |Cite
|
Sign up to set email alerts
|

Pseudotumours associated with metal-on-metal hip resurfacings

Abstract: We report 17 patients (20 hips) in whom metal-on-metal resurfacing had been performed and who presented with various symptoms and a soft-tissue mass which we termed a pseudotumour. Each patient underwent plain radiography and in some, CT, MRI and ultrasonography were also performed. In addition, histological examination of available samples was undertaken. All the patients were women and their presentation was variable. The most common symptom was discomfort in the region of the hip. Other symptoms included sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
731
5
11

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 904 publications
(763 citation statements)
references
References 15 publications
16
731
5
11
Order By: Relevance
“…Periprosthetic soft tissue lesions around MOM hip implants have been reported by numerous authors using various terms including ALTR, ARMD, ALVAL, metallosis, and pseudotumor [1,17,23,24,33]. These soft tissue masses can be associated with major tissue destruction [24] and therefore early recognition and prompt revision are critical.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Periprosthetic soft tissue lesions around MOM hip implants have been reported by numerous authors using various terms including ALTR, ARMD, ALVAL, metallosis, and pseudotumor [1,17,23,24,33]. These soft tissue masses can be associated with major tissue destruction [24] and therefore early recognition and prompt revision are critical.…”
Section: Discussionmentioning
confidence: 99%
“…These soft tissue masses can be associated with major tissue destruction [24] and therefore early recognition and prompt revision are critical. Our aims were to identify which MRI characteristics correlated with the ALVAL score and intraoperative tissue damage and to develop a predictive model using modified MRI to detect ALVAL as confirmed by histology and to quantify intraoperative tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ALVAL has been described in the setting of MOM total hip arthroplasty and MOM hip resurfacing arthroplasty (51)(52)(53) and may manifest as synovitis, bursitis, periprosthetic osteolysis, and cystic or solid masses, which have previously been termed ''pseudotumors'' (53,54).…”
Section: Metal-on-metal-bearing Surfacesmentioning
confidence: 99%
“…The exact prevalence of hypersensitivity reactions following MOM arthroplasties is unknown but in larger retrospective studies ''pseudotumors'' have been reported in up to 1% of patients with MOM hip resurfacing arthroplasty at revision surgery (52,53). The incidence may in fact be higher than this on imaging, as ''pseudotumors'' can occur in asymptomatic patients (53)(54)(55).…”
Section: Metal-on-metal-bearing Surfacesmentioning
confidence: 99%